Recent Development of Nanomaterial-Doped Conductive Polymers - Asyraf, M.; Anwar, M.; Sheng, L.; Danquah, Michael (The Minerals, Metals and Materials Society, 2017)
© 2017, The Minerals, Metals & Materials Society. Conductive polymers (CPs) have received significant research attention in material engineering for applications in microelectronics, micro-scale sensors, electromagnetic shielding, and micro actuators. Numerous research efforts have been focused on enhancing the conductivity of CPs by doping. Various conductive materials, such as metal nanoparticles and carbon-based nanoparticles, and structures, such as silver nanoparticles and graphene nanosheets, have been converted into polypyrrole and polypyrrole compounds as the precursors to developing hybrids, conjugates, or crystal nodes within the matrix to enhance the various structural properties, particularly the electrical conductivity. This article reviews nanomaterial doping of conductive polymers alongside technological advancements in the development and application of nanomaterial-doped polymeric systems. Emphasis is given to conductive nanomaterials such as nano-silver particles and carbon-based nanoparticles, graphene nano-sheets, fullerene, and carbon nanotubes (CNT) as dopants for polypyrrole-based CPs. The nature of induced electrical properties including electromagnetic absorption, electrical capacitance, and conductivities of polypyrrole systems is also discussed. The prospects and challenges associated with the development and application of CPs are also presented.